Pengaruh Penggunaan Media Flash Card Terhadap Hasil Belajar SKI Siswa MTS Swasta NU Sorkam Kanan Di Sumatera Utara - Imliana Tantri Marbun; Arifmiboy Arifmiboy; Salmi Wati; Muhiddinur Kamal (Pusat Riset dan Inovasi Nasional, 2023)
Based on information from the teachers, the students’ SKI learning outcomes are low. The reason for this is that using varied teacher media will result in students learning to feel bored and less enthusiastic and students become passive. The purpose of this research was conducted at private MTs N’L sorkam kanan in North Sumatera to be precise, students in class IX.A and IX.B. It can be seen that in the learning carried out after using flash card media on student SKI learning outcomes. This study used experimental research where class IX B was used as an experimental class. The class was given treatment using flash card media with a total of 24 students and for the control class, class IX.A was not given treatment but only used conventional media. As every day in learning, the number of students here is 26 students will be seen that there is a good differences in the results when using flash card media with conventional media. So with that, trials were carried out with preter and portert tests to find out differences in students SKI learning outcomes before and after being given treatment. Flash card media on the learning outcomes of SKI MTs Students private MTs NU Sorkam right in North Sumatra, which was seen in a paired t test with editorial T1 pretest and T2 posttest which produces sig= 0,000 which is smaller than the significant 0,05 and the tcount test is 10,021 while the t tabel of 24 students, the t tabel is 0,173 then Ha is accepted. 2. There are differences in student SKI learning outcomes using flash card media and conventional media as shown at sig= 0,018 which is smaller than the significant 0,05. 3. Student SKI learning outcomes using flash card media are better than conventional media seen at it sig=0,018 which is smaller than the significant 0,05 can be seen that student SKI learning outcomes using flash card media are better than conventional media.